2020
DOI: 10.17755/esosder.671003
|View full text |Cite
|
Sign up to set email alerts
|

Fi̇bromi̇yalji̇ Sendromu Tanili Kadinlarda Psi̇kodrama Grup Terapi̇si̇ni̇n Ağri, Depresyon Ve Yaşam Doyumu Üzeri̇ne Etki̇leri̇

Abstract: Psikodrama grup terapisi uygulaması ile, fibromiyalji sendromu tanısı alan kadınların, duygu ifadeleri sağlanarak ağrılarının ve eşlik eden depresyonlarının azalıp yaşam doyumlarının artması amaçlanmıştır. Çalışma, fizik tedavi ve rehabilitasyon polikliniğinden yönlendirilen, fibromiyalji sendromu tanılı, 15 hastayla başlamış, 12 hastayla tamamlanmıştır. Oturumlar; haftada bir gün, 11 hafta boyunca yapılmıştır. Etkin kullanılan teknikler; rol değiştirme, aynalama ve eşlemedir. Hastalara psikodrama grup çalışma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Accompanied by widespread body pain and many other symptoms, fibromyalgia whose etiology is still largely unclear (Friedberg, 2010;Hauser et al, 2015;Heidari et al, 2017) causes serious difficulties in individuals' daily life activities and their functional capacity and impairs their physical and emotional quality of life (Ataoğlu et al, 2017). The lives of these patients, who go from doctor to doctor to find a cure for their pain, come to a dead-end in direct ways such as through prescriptions and nutritional supplements, or come to an end indirectly such as through inadequacies in business life and job loss (Altınkılıç et al, 2020;Spaecth, 2009;Wassem & Hendrix, 2003). Since the effect of chronic diseases on individuals' quality of life cannot be denied, it is important to treat the diseases and their symptoms and to increase the quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanied by widespread body pain and many other symptoms, fibromyalgia whose etiology is still largely unclear (Friedberg, 2010;Hauser et al, 2015;Heidari et al, 2017) causes serious difficulties in individuals' daily life activities and their functional capacity and impairs their physical and emotional quality of life (Ataoğlu et al, 2017). The lives of these patients, who go from doctor to doctor to find a cure for their pain, come to a dead-end in direct ways such as through prescriptions and nutritional supplements, or come to an end indirectly such as through inadequacies in business life and job loss (Altınkılıç et al, 2020;Spaecth, 2009;Wassem & Hendrix, 2003). Since the effect of chronic diseases on individuals' quality of life cannot be denied, it is important to treat the diseases and their symptoms and to increase the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Another psychodrama study conducted with individuals with psychosomatic disorders concluded that the pain levels of the group members decreased and they felt more relaxed due to psychodrama (Bal & Şener, 2015). In another psychodrama study conducted with women with fibromyalgia, it was determined that the participants' belief in recovery and self-confidence, as well as their ability to express suppressed emotions increased (Altınkılıç et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…181 There are many studies in which psychodrama is used both as a method and a technique in individual, group, and family therapies; psycho-education; personal development and interaction groups; and Bibliodrama (a form of role-playing or improvisational theater using Bible stories). Studies have tested its effectiveness on various populations and subject/problem areas, from vocational training to the teaching of course subjects in schools, from children to the elderly, from students to teachers, from nurses to counselors, and from undiagnosed/healthy individuals to diagnosed/disadvantaged individuals (Avest, 2017;Dorothea, 2016;Wieser, 2013;Okur Berberoğlu, 2017;Abu Al Rub, 2018;Maya, Jiménez, Lorence, del Moral and Hidalgo, 2020;Farmer and Geller, 2005;Prima, Putri and Sudargo, 2017;Çoşkun and Çakmak, 2005;Altınkılıç, Ateşçi and Uğurlu, 2020;Karadağ, Kalkan Oğuzhanoğlu, Özdel, Ergin and Kaçar, 2010;Akbıyık, Soygür and Karabulut, 2012;Varma, Karadağ, Kalkan Oğuzhanoğlu and Özdel, 2017;Çiçek, 2019;Konopik and Cheung, 2012;Kılıç, 2019;Parkan, 2015;Gürgan, 2020;Kalkan Oğuzhanoğlu and Özdel, 2005;Aktaş, 2014;Gökkaya and Özdel, 2016;Göveç Taşpınar, 2014;Çınar, 2011;Karataş, 2008;Karataş, 2011;Karataş and Gökçakan, 2009;Orkibi, 2011;Dorethea, 2016;Bakalım, Yörük and Şensoy, 2018;Durmuş, 2019;Şener, 2018;Aytan Erdoğan, 2010;Hamamcı, 2002;Gürgan, 2006;Karataş, 2014;…”
mentioning
confidence: 99%